Math problem. College Algebra?

Math help... College Algebra
1. (2a-b) (2a-b) I got 2a^2-b^2. Am I right?
2. 2 (5-8)^2-10/2 I got 4. Am I right?
3. Given g (x)=-x^2+2x-4, find g (-a) I got g (-a)=a^2+2a-4


0|0
3|2

Most Helpful Girl

  • 1. (2a-b)(2a-b)
    = 4a^2-2ab+b^2
    2. 2(5-8)^2-10/2
    = 2*(-3)^2-5
    = 2*9-5
    = 13
    3. g (x)=-x^2+2x-4
    = g (-a)=-(-a)^2-2a-4

    0|0
    0|0

What Guys Said 2

  • 1.) This uses the FOIL (First, outside, inside, last) system, where each term of one polynomial is multiplied with each term with the other polynomial. So.

    (2a-b)*(2a-b) can be broken down to FIRST: (2a*2a) + OUT: (2a*-b) + IN: (-b*2a) + LAST: (-b*-b) which will become 4a^2 + (-2ab) + (-2ab) + (b^2). Add the like terms to give the final answer of 4a^2 - 4ab + b^2

    2.) 2*(5-8)^2-10/2

    This questions uses PEMDAS (Parenthesis, Exponents, Multiplication, Division, Addition, Subtraction in that order)

    So with 2*(5-8)^2-10/2 we have parenthesis (5-8) = (-3). There is an exponent (-3)^2 which becomes +9. Now we have 2*9 - (10/2). Using multiplication and division, the equation can be simplified to 18 - 5, which is equal to 13.

    3.) Given g (x)=-x^2+2x-4, find g (-a)

    This problem is simple as it simply wants you to insert (-a) wherever there is an (x). So it becomes (-(-a))^2 + 2(-a) - 4, which can be simplified to a^2 - 2a -4.

    1|0
    0|0
  • Not at all, it's

    First one: (2a-b)(2a-b) = 4a^2 - 4ab + b^2
    Second one: 2*(5-8)^2 - 10/2 = 2 * (-3)^2 - 5 = 2 * 9 - 5 = 13
    Third one: g (x) = -x^2 + 2x - 4 at g (-a) is -(-a)^2 + 2*(-a) - 4 = -a^2 -2a -4

    0|0
    0|0

What Girls Said 2

  • 1. 4a^2-4ab+b^2-do the foil method
    2. 13-pemdas
    3. correct

    0|0
    0|0
  • College Algebra? My ass
    This is 8th grade maths.

    2|1
    0|0
Loading...